Comparative Study of Credit Risk, Liquidity Risk, and Market Risk in Banking in Indonesia, Malaysia, and Thailand - Cici Widya Prasetyandari; Zahida I’tisoma Billah (Journal of Islamic Economics Lariba, 2021)
The purpose of this study was to determine the differences in financial risk in several banks in Indonesia, Malaysia and Thailand. The population of this research is all commercial banks in Indonesia, Malaysia and Thailand. The sample selection technique used is purposive sampling. The analytical tool in this study is a comparative analysis with the Kruskal-Willis test. The results showed that there were significant differences in the NPL, LDR, and NIM variables of banking in Indonesia, Malaysia and Thailand.